War Powers : the Politics of Constitutional Authority - Zeisberg, Mariah Ananda, 1977- (Princeton University Press, 2013)
Armed interventions in Libya, Haiti, Iraq, Vietnam, and Korea challenged the US president and Congress with a core question of constitutional interpretation: does the president, or Congress, have constitutional authority to take the country to war? War Powers argues that the Constitution doesn't offer a single legal answer to that question. But its structure and values indicate a vision of a well-functioning constitutional politics, one that enables the branches of government themselves to generate good answers to this question for the circumstances of their own times.